Understanding "expert" scientists: Implications for management and organization research. Issue 5 (November 2019) - Dörfler, Viktor; Eden, Colin
This article contributes to the debate about rigor and relevance in management and organization research. The contribution derives from an empirical inquiry into the view of the research process of acknowledged experts in scientific research: Nobel Laureates. The research was conducted through loosely structured in-depth interviews with, and background information about, 19 of these expert researchers. The analysis of the interviews suggests emergent themes of the process of successful research that are likely to be relevant to the conduct of management and organization research. We focus on three themes from our interviews: the role of the "big leap" and its relationship to intuition; the significance of seeing both the "big picture" and the detail; and the ways of building and developing successful research teams. We set out our findings from the interviews in the context of the literature from history and philosophy of science and examine the implications for management and organization research.